2008
DOI: 10.1088/1742-5468/2008/12/p12009
|View full text |Cite
|
Sign up to set email alerts
|

The probability distribution of internal stresses in externally loaded 2D dislocation systems

Abstract: Abstract. The distribution of internal shear stresses in a 2D dislocation system is investigated when external shear stress is applied. This problem serves as a natural continuation of the previous work of Csikor and Groma (Csikor F F and Groma I 2004 Phys. Rev. B 58 2969), where analytical result was given for the stress distribution function at zero applied stress. First, the internal stress distribution generated by a set of randomly positioned ideal dislocation dipoles is studied. Analytical calculations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…In a simplified model used in this paper only parallel edge dislocations are considered with a single glide plane. Although in crystals dislocations usually form complex three-dimensional networks, this model proved capable of reproducing many experimentally observed phenomena related to plasticity, like, e.g., strain avalanche statistics [1], Andrade-creep exponents [2,3], and properties of X-ray profiles [4,5].…”
Section: Introductionmentioning
confidence: 96%
“…In a simplified model used in this paper only parallel edge dislocations are considered with a single glide plane. Although in crystals dislocations usually form complex three-dimensional networks, this model proved capable of reproducing many experimentally observed phenomena related to plasticity, like, e.g., strain avalanche statistics [1], Andrade-creep exponents [2,3], and properties of X-ray profiles [4,5].…”
Section: Introductionmentioning
confidence: 96%
“…It was also shown that the central part of the PDF is Gaussian and Cauchy for homogeneous and uncorrelated systems of straight infinite edge dislocations and dipolar configurations, respectively [40]. Both the central and asymptotic parts of stress distribution are shown to be affected by the external shear stress [41]; the central part becomes asymmetric and shifted by an amount proportional to the applied stress, and the asymptotic part becomes dependent on an extra term that decays with inverse forth power of stress. In a related work, an analytical expression of pair correlation of internal stress was proposed in [42] in which the stress fluctuation is directly connected to the dislocation density fluctuation.…”
Section: Introductionmentioning
confidence: 98%
“…The works reported in [39][40][41] are of direct relevance to the current work for they include an analysis of the internal shear stresses of straight parallel dislocation arrangements in terms of probability density functions (PDF). Under zero external stress, it is was shown that the asymptotic behavior of the PDF of stress is only dependent on the local dislocation density, and it decays with the inverse third power of the stress [39].…”
Section: Introductionmentioning
confidence: 99%
“…This idea led to the development of a statistical description of dislocation dynamics based on pair correlation functions, as first done by Groma [36] in the context of X-ray line broadening due to disordered distributions of dislocations and, subsequently, by Groma and Bakó [37] with stochastic ensembles of parallel edge dislocations. Further work by El Azab [18], Zaiser et al [38], Kratochvíl and Sedlácek [19] amongst many others, have focused on computing the pair correlation functions describing the dislocation density distribution and the general probability distribution functions, aiming at describing plasticity evolution laws (see [39][40][41]), and the energetics of dislocation ensembles [42][43][44]. Recently, Berdichevsky [45] has offered an expression for the regularised energy of a random set of dislocation lines, Zaiser [44] used an elastic energy functional approximation to study two and three dimensional ensembles of dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…In the statistical approach developed by Groma and coworkers [37], the stress state is obtained from the probability distribution of the stress field, which in turn is dependent on the conditional probability to find dislocations at a given location, and is therefore not available in a general case [46], but may be obtained from X-ray diffraction data, dislocation dynamics simulations [39,40], or for specific kinds of dislocation ensembles [41,47]. For instance, Csikor and Groma [47] computed it for disperse arrangements of uncorrelated dislocation dipoles.…”
Section: Introductionmentioning
confidence: 99%